1986
DOI: 10.1007/bf01799703
|View full text |Cite
|
Sign up to set email alerts
|

Problems related to diet management of maternal phenylketonuria

Abstract: Provision of nutritionally complete elemental diets for pregnant women with PKU requires greater knowledge of 'conditionally' essential nutrient requirements than is presently available as well as application of known information. Formulation of elemental products needs to be improved to enhance aroma and taste and to decrease osmolality. Designers of the metal and vitamin components should keep in mind that a major portion (70-80%) of most of these nutrients must be obtained from the elemental products. Thus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1988
1988
2007
2007

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 90 publications
0
2
0
Order By: Relevance
“…In fact, it has been observed that this type of diet may produce nutritional deficits (Acosta and Stepnick-Gropper 1986), with consequences for growth and development. Studies highlight inadequate intake of taurine (Agostoni et al 1990), carnitine (Schulpis et al 1990) and other micronutrients mostly contained in animal-derived food that is not permitted in the diet of PKU patients.…”
Section: Characteristics Of the Pku Dietmentioning
confidence: 99%
“…In fact, it has been observed that this type of diet may produce nutritional deficits (Acosta and Stepnick-Gropper 1986), with consequences for growth and development. Studies highlight inadequate intake of taurine (Agostoni et al 1990), carnitine (Schulpis et al 1990) and other micronutrients mostly contained in animal-derived food that is not permitted in the diet of PKU patients.…”
Section: Characteristics Of the Pku Dietmentioning
confidence: 99%
“…Acosta and Stopnick-Gropper (34) have discussed the physicochemical problems which can result from the osmolality of the various available amino acid solutions. A typical mixture for the phenylketonuric mother which provides the equivalent of 60 g protein daily and is diluted to 500 ml with water will have an osmolality of around 1900 mosm/kg water.…”
Section: Dietary Managementmentioning
confidence: 99%